The influence of cost at production inputs on farmer income at chili pepper commodity in Sub-District Dungaliyo Gorontalo Regency - Amir Halid; Yuriko Boekoesoe; Ratna Mohune (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
The research objective is 1) To analyze the earning of farmer of chili at Dungaliyo Sub-District in Gorontalo Regency; 2) To analyze of using cost in production influenced at farmer’s chili earning at Dungaliyo Sub-District Gorontalo Regency. The population is all of the chili pepper farmers in the sub-district Dungaliyo of Gorontalo Regency, wheter the sample is about 42 people. Descriptive analysis was used to analyze the earning of farmer of chili. Multiple regression model was used to analyze factors affecting income farming. The results showed that (1) revenue gained by chili pepper farmers in sub Dungaliyo Gorontalo district average Rp. 9166666.7 with value/ha Rp. 2.037,037.44 and the total cost is Rp. 4.233,961.905 with value/ha Rp. 940,880.2 net income of farmers of chili pepper Rp. 4,932,704.762 with value/ha Rp. 1,096,156,- (2) The results of multiple regression analysis showed that the cost of production facilities impact on farm income chili pepper in Sub-district Dungaliyo such as equipment rental costs and agricultural machinery (X1) the significant value <0.01 was highly significant, costs fertilizers (X2) the significant value <0.01 highly significant, Cost Drugs – drugs (X3) significant value <0.05 was significant, and the cost of seed (X4) the significant value <0.01 was highly significant in the farming chili pepper. Keywords: Production input cost, Revenue, Chili pepper